2016
DOI: 10.1016/j.bbadis.2016.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of FUS interacting proteins provides insights into FUS function and its role in ALS

Abstract: Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease. Mutations in the Fused in Sarcoma/Translocated in Liposarcoma (FUS/TLS) gene cause a subset of familial ALS cases and are also implicated in sporadic ALS. FUS is typically localized to the nucleus. The ALS-related FUS mutations cause cytoplasmic mis-localization and the formation of stress granule-like structures. Abnormal cytoplasmic FUS localization was also found in a subset of frontotemporal dementia (FTLD) cases without FUS mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
99
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(111 citation statements)
references
References 84 publications
(88 reference statements)
7
99
0
Order By: Relevance
“…Interestingly, we (this study, see Fig. 2 (PARP1) and Supplementary Table 1) and others (Blokhuis et al, 2016;Bosco et al, 2010;Kamelgarn et al, 2016;Sun et al, 2015) reported interactions between FUS and different stress granule markers. Hence, it is conceivable that LLPS-deficient FUS sequesters factors required for the formation of stress granules and thus prevents the formation of stress granules during stress.…”
Section: Llps Is Not Required For Fus Toxicity In the Cytoplasmsupporting
confidence: 54%
See 2 more Smart Citations
“…Interestingly, we (this study, see Fig. 2 (PARP1) and Supplementary Table 1) and others (Blokhuis et al, 2016;Bosco et al, 2010;Kamelgarn et al, 2016;Sun et al, 2015) reported interactions between FUS and different stress granule markers. Hence, it is conceivable that LLPS-deficient FUS sequesters factors required for the formation of stress granules and thus prevents the formation of stress granules during stress.…”
Section: Llps Is Not Required For Fus Toxicity In the Cytoplasmsupporting
confidence: 54%
“…Nevertheless, many FUS interactors are detected under both conditions but show a clear preference for either dispersed/soluble or phase separated FUS.. Importantly, several proteins enriched with phase separated FUS, such as DDX3X, DHX9, FMR1, TIAR-1 and SMN1 (compare Supplementary Table 1), have already been observed by others to co-localize with FUS into cytoplasmic granules (Blokhuis et al, 2016;Bosco et al, 2010;Groen et al, 2013;Kamelgarn et al, 2016). Moreover, proteins found in nuclear granules, specifically paraspeckles (Shelkovnikova et al, 2014) and transcription-dependent granules containing FUS and RNA Pol II (Thompson et al, 2018) are highly enriched under LLPS conditions compared to non-LLPS conditions (compare data in Supplementary Table 1).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…; Kamelgarn et al . ; Yamaguchi & Takanashi ), future studies should address how Matrin3 and TDP‐43 or FUS coordinately regulate alternative splicing and how disease‐associated point mutations in MATR3 affect binding to TDP‐43 or FUS in terms of the elucidation of disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It remains undetermined whether disease-associated point mutations in MATR3, which are located outside the RRMs, affect the regulation of splicing by Matrin3. Given that dysregulation of splicing is induced by ALS-linked point mutations in TARDBP and FUS (Arnold et al 2013;Reber et al 2016) and that Matrin3 associates with TDP-43 and FUS (Ling et al 2010;Salton et al 2011;Johnson et al 2014;Kamelgarn et al 2016;Yamaguchi & Takanashi 2016), future studies should address how Matrin3 and TDP-43 or FUS coordinately regulate alternative splicing and how diseaseassociated point mutations in MATR3 affect binding to TDP-43 or FUS in terms of the elucidation of disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%